EU cohesion policy and the equity-efficiency trade-off - Adding dynamics to Martin's model - Dietmar Meyer; Jörg Lackenbauer (European Regional Science Association (ERSA), 2005)
As a result of the combination of endogenous growth theory with the approach of the new economic geography (NEG), several models have been developed to explain spatial income inequality and to formulate possible policy strategies taking into account the equity-efficiency trade-off. The dynamics of this problem should be considered as fundamentally important for the enlargement of the EU, because with respect to the new Member States from Central and Eastern Europe (CEECs), EU cohesion policy is confronted with a double challenge: how can it contribute to attain higher national growth (and therefore convergence towards the EU average income per capita) and at the same time contribute to the decrease of regional disparities within the new Member States? This analysis is particularly appealing against the background of the alleged equity-efficiency trade-off that regional policies often suffer from. After the introduction, in the second part of this paper, some light is shed on this equity-efficiency trade-off in the framework of an overview surveying the theoretical literature on the issue. In the third part of the paper, a model presented by Philippe Martin (1999) is presented. Martin's model combines the approaches of NEG and endogenous growth theory. In the fourth part, we develop a very simple dynamic version of the Martin model, followed by its formal analysis. We examine the effect of a monetary transfer to the poorer region, financed by the EU in the context of its cohesion policy interventions. In the fifth part, we derive some regional policy implications of the dynamised version of the Martin model. We find that there is a case for a "two step regional policy approach” in order to tackle the equity-efficiency trade-off challenge: this approach first aims to support the richer region and thus aggregate growth in the whole integrated area, and then to pursue an equity-oriented cohesion policy by fostering firm creation and innovation in the poorer region.
Keywords: 330